Key Drivers of Performance Accountability in the Batola Regional Government Agency, South Kalimantan Province-Indonesia - Noor, Syamsu Rizal; Respati, Novita Weningtyas; Nor, Wahyudin (Ilomata International Journal of Management, 2024)
This study's primary goal is to identify the variables that affect Batola Regency local government agencies' performance. Barito Kuala Regency received a good predicate based on the results of the Ministry of Administrative and Bureaucratic Reform of the Republic of Indonesia's SAKIP category announcement. However, Several SKPDs did not adhere to it, even though their reports on the findings of the government agency performance accountability assessment still had a strong enough foundation. Thus, a study about this phenomenon is required to ascertain the degree of responsibility of government agency performance in SKPD Barito Kuala Regency. The difference between this study and previous studies lies in the research variables on compliance with laws and regulations. The study's findings show that the clarity of budget targets, accounting control, and reporting systems have a significant impact on the performance accountability of government agencies in Barito Kuala Regency, whereas compliance with laws and regulations has no effect. The preparation of specific budget targets will facilitate the achievement of budget targets and as accounting control. The local government monitors and assesses all activities whether they are economical, efficient, and effective in providing services to the community. A good reporting system is needed to provide information on performance that is easily accessible to interested parties. Resulting in strong performance accountability of government agencies in Barito Kuala Regency.